NEW NORMAL PADA INDUSTRI PERBANKAN DI TENGAH PANDEMIK COVID-19 - Kurniawan, I Gede Hartadi; Judge, Zulfikar; Olivia, Fitria (Universitas Esa Unggul, 2020)
Large-scale Social Restrictions (PSBB) that have been imposed in several regions of Indonesia have passed several times of extension from one period to the next. In the DKI Jakarta area, on June 5, 2020 passed the third period and entered the fourth period PSBB or also called the transition PSBB period or if it was likened to another term, the